p53 upregulation is a frequent response to deficiency of cell-essential genes. - Nadia Danilova; Asako Kumagai; Jenny Lin (PLoS ONE)
Background The role of p53 in the prevention of development of embryos damaged by genotoxic factors is well recognized. However, whether p53 plays an analogous role in preventing birth defects from genetic mutations remains an unanswered question. Genetic screens for mutations affecting development show that only a fraction of developmentally lethal mutations leads to specific phenotypes while the majority results in similar recurrent phenotypes characterized by neuronal apoptosis and developmental delay. Mutations in cell-essential genes typically fall into this group. The observation that mutations in diverse housekeeping genes lead to a similar phenotype suggests a common mechanism underlying this phenotype. For some mutants, p53 inhibition was shown to attenuate the phenotype. Methodology/principal findings To find out how common p53 involvement is in this phenotype, we analyzed zebrafish mutants from various categories of cell essential genes. Several thousand zebrafish mutants have been identified; many of them are kept at stock centers and available for the research community. We selected mutants for genes functioning in DNA replication, transcription, telomere maintenance, ribosome biogenesis, splicing, chaperoning, endocytosis, and cellular transport. We found that mutants have similar phenotypes including neural apoptosis, failure to develop structures originated from the neural crest cells, and hematopoietic defects. All mutants share p53 upregulation and similar changes in several p53-dependent and independent molecular pathways. Conclusion/significance Our results suggest that mutations in housekeeping genes often canalize on the p53-mediated phenotype. p53 prevents the development of embryos with defects in such genes. p53-mediated changes in gene expression may also contribute to many human congenital malformations.